Pengaruh Kualitas Pelayanan Waroeng Spesial Sambal H. Syaifulloh Terhadap Kepuasan Konsumen - AGUSTINA, DEMA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Competition in the business world is now increasingly stringent, it is also felt by businesses such culinary Waroeng H. Syaifulloh Spesial Sambal. In order for customers to feel satisfied and not move to another place, then the company must serve the customer with excellent service, customer satisfaction can be created because of the good service quality.This study examined how much the influence of service quality on customer satisfaction. purpose of this study is to determine how much influence the quality of service to the satisfaction of this konsumen.Penelitian using quantitative descriptive research, this study used a sample of 110 respondents and data collection was conducted by questionnaire to 110 respondents Waroeng Spesial Sambal H. Syaifulloh by using purposive sampling.This research based on the results of test of determination coeficient regretion, it can be seen the influence of service quality on customer satisfaction was 60.9%. Then through the test T is also known that the effect of service quality on customer satisfaction supported by 12.969 with a significance level of 0.000 <0.05 or 5%, it indicates that service quality has a significant influence on customer satisfaction. Keywords: Quality of service, customer satisfaction